2020
DOI: 10.3390/ijms21207453
|View full text |Cite
|
Sign up to set email alerts
|

Proteome Analysis of Walnut Bacterial Blight Disease

Abstract: The interaction between the plant host, walnut (Juglans regia; Jr), and a deadly pathogen (Xanthomonas arboricola pv. juglandis 417; Xaj) can lead to walnut bacterial blight (WB), which depletes walnut productivity by degrading the nut quality. Here, we dissect this pathosystem using tandem mass tag quantitative proteomics. Walnut hull tissues inoculated with Xaj were compared to mock-inoculated tissues, and 3972 proteins were identified, of which 3296 are from Jr and 676 from Xaj. Proteins with differential a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 92 publications
0
4
0
Order By: Relevance
“…The searches used semi-tryptic cleavage, 1.25 Da precursor mass tolerance, 1.0005 Da fragment ion tolerances, variable oxidation of methionine, and static modifications for alkylated cysteines and TMT tags (at peptide N-term and lysine). The proteomic analysis workflow (PAW) pipeline was used for peptide spectrum match (PSM) validation using the target/decoy method as previously described [ 24 ]. Basic parsimony and extended parsimony analyses were performed to obtain the final protein groups.…”
Section: Methodsmentioning
confidence: 99%
“…The searches used semi-tryptic cleavage, 1.25 Da precursor mass tolerance, 1.0005 Da fragment ion tolerances, variable oxidation of methionine, and static modifications for alkylated cysteines and TMT tags (at peptide N-term and lysine). The proteomic analysis workflow (PAW) pipeline was used for peptide spectrum match (PSM) validation using the target/decoy method as previously described [ 24 ]. Basic parsimony and extended parsimony analyses were performed to obtain the final protein groups.…”
Section: Methodsmentioning
confidence: 99%
“…Abdelrahman et al (2017) found that SA signaling-related genes PR1 and JA biosynthesis and signaling-related genes PLDa1 (phospholipase D alpha 1), OPR (12-oxophytodienoate reductase), and JIP23 (jasmonate-induced protein 23 KD) were upregulated in resistant wild Asparagus kiusianus stems relative to susceptible A. officinalis after P. asparagi infection. Sagawa et al (2020) found that the PR proteins PR1, PR2, PR3, and PR5 significantly accumulated in walnut fruits with Xaj infection, and moreover, the ethylene biosynthesis proteins 1-aminocyclopropane-1-carboxylate oxidase (ACC) and S-adenosylmethionine synthase (SAM) were increased. The qRT-PCR validation of selected genes.…”
Section: Discussionmentioning
confidence: 99%
“…Solar et al (2006) found that seasonal variations in phenolic compounds in annual shoots have a greater influence than phenolic content on the susceptibility of the shoots to walnut blight pathogens. Sagawa et al (2020) performed proteome analysis using Chandler walnut (J. regia) fruits inoculated with Xaj and found that the infection enhanced oxidative stress and degradation processes, and biosynthetic metabolism was inhibited in the fruits. In addition, phytohormone-associated defense proteins changed after infection.…”
Section: Introductionmentioning
confidence: 99%
“…They play a significant role in human, animal, and plant health because these compounds have antioxidant and antiradical properties. They exhibit anticarcinogenic, antimutagenic, anti-inflammatory, cardioprotective, astringent, antiseptic, anthelmintic, and antiaging effects that are beneficial to human and animal health [45,[104][105][106][107][108].…”
Section: Effects Of Walnut Green Husk Biochemical Compounds On Abioti...mentioning
confidence: 99%